2017
DOI: 10.3389/fmicb.2016.02171
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis and Bacillus weihenstephanensis Inhibit the Growth of Phytopathogenic Verticillium Species

Abstract: Verticillium wilt causes severe yield losses in a broad range of economically important crops worldwide. As many soil fumigants have a severe environmental impact, new biocontrol strategies are needed. Members of the genus Bacillus are known as plant growth-promoting bacteria (PGPB) as well as biocontrol agents of pests and diseases. In this study, we isolated 267 Bacillus strains from root-associated soil of field-grown tomato plants. We evaluated the antifungal potential of 20 phenotypically diverse strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 100 publications
4
34
0
4
Order By: Relevance
“…In this study, we assessed the effect of KNU-07 on the growth of pepper plants and the soil bacterial community and designed a strain-specific primer pair to track the population dynamics of KNU-07 in soil using a qPCR-based method. Similar to the results of our in vitro assays, IAA production, siderophore production, phosphate solubilization, and urease activity by several strains of B. thuringiensis have been previously reported [12][13][14]. An increase in IAA production in the presence of L-tryptophan may attributed to the nature of the strain to utilize L-tryptophan as a physiological precursor [35].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we assessed the effect of KNU-07 on the growth of pepper plants and the soil bacterial community and designed a strain-specific primer pair to track the population dynamics of KNU-07 in soil using a qPCR-based method. Similar to the results of our in vitro assays, IAA production, siderophore production, phosphate solubilization, and urease activity by several strains of B. thuringiensis have been previously reported [12][13][14]. An increase in IAA production in the presence of L-tryptophan may attributed to the nature of the strain to utilize L-tryptophan as a physiological precursor [35].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, although the effect of PGPR on the indigenous soil bacterial communities and their functional properties has been studied, there is very limited information on the effects of B. thuringiensis on bacterial communities in the soil [10,11]. The beneficial effects of B. thuringiensis on plants are due to direct and indirect mechanisms, including nitrogen fixation, siderophore production, plant nutrient solubilization, and plant growth hormone production [12][13][14]. However, the plant responses are often variable due to inconsistent performance of inoculants under field conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of B. thuringiensis have shown antifungal potential in dual cultivation assays. For example, Hollensteiner et al (2017) showed in vitro antagonism toward Verticillium dahlia, a pathogen with a broad host range, including economically important crops such as tomato. The authors suggested that the inhibitory effect on the growth of the phytopathogens was attributed to the presence of chitinases in the supernatant of the bacterial culture.…”
Section: Application Of Chitinases To Improve the Toxic Activity Agaimentioning
confidence: 99%
“…Biological structures made of chitin are prime targets for chitinolytic enzymes, and as such, phytopathogenic fungi or pest insects are susceptible to degradation by chitinases (Morales de la Vega et al, 2006;Juárez-Hernández et al, 2015;Hollensteiner et al, 2017). Chitinases are produced and secreted by viruses, prokaryotes, and eukaryotes, including humans, plants, fungi, and insects, which interestingly may or not have chitin.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus anthracis and Bacillus cereus can not only synthesize Bacillibactin, but also synthesize Petrobactin. The complete Bacillibactin and Petrobactin synthesis gene cluster have been found in the genome of Bacillus thuringiensis (Wilson et al, 2006;Hollensteiner et al, 2016). Bacterial siderophore is not only a wide variety of species, but also a variety of functions.…”
Section: Introductionmentioning
confidence: 99%